Comportamento do peixe Astronottus ocellatus (Agassiz, 1861) submetidos a enriquecimento em aquário - Oliveira, Ana Paula Guedes (2016)
The objective was to analyze the preference of the oscar fish, Astronotus ocellatus (Pisces, Cichlidae) by the provision in the aquarium substrate types, vegetation, shelter and color, and draw up a ethogram and compare the behavior of those in aquaria without environmental enrichment and environmental enrichment. A total of 30 fish during the experiment, and for preference tests were used 16. The animals were approximately 13 months old, average weight and length of 17.4 ± 1.13 g and 9.73 ± 1.04 cm, and were acclimated before insertion in aquariums. Observation of focal animal type were made. For the preference test was considered regions of the aquarium, the types of substrate, vegetation, shelter and color. The observations lasted 51 hours. The design was completely randomized with five treatments and four replications, and the results analyzed using the chi-square test and compared the even frequencies by SAS statistical software. Among the offered objects, the fish have a preference for corners and aquarium bottom, shells and sand, frog plant and tile, blue, yellow and green. The ethogram was elaborated with the following behaviors: pushing, swimming alone, swimming in shoals, rub, rub object, halter, beat, throw down, nibble, agitation, squeezing, spreading, hiding behind the plant, stop apathetichole group, hide, aquarium corner, scare digbed in hole, swim over the hole, eat, attack, view the exterior, plant break and change color. Most non agonistic natural behaviors were observed in the aquarium without environmental enrichment, except d eating behavior had a frequency of 0.7% in the aquarium without enrichment and 1.5% in the enriched aquarium. The agonistic natural behaviors, in turn, were more common in the aquarium without environmental enrichment, and only the behaviors rub on other fish and stick group were observed at a frequency of 3.9% and 0.2% consecutively in aquarium with environmental enrichment. Anomalous behaviors were more common in the aquarium without environmental enrichment. Preference tests showed that Astronotus ocellatus preferred the bottom and corners of aquariums and opted for shells and sand substrates. They chose Heteranthera reniformis and tile as they allow better refuge. Also chose the color blue to favor the expression of natural behavior. This study was important because it favors the development of experimental protocols for behavioral studies with oscar fish. Furthermore, it allowed the development of a ethogram for the species consisting of relevant acts and to demonstrate the importance of environmental conservation in the preservation of the species. The results also demonstrate the effectiveness of low cost and easy acquisition environmental enrichment in the expression of natural behavior of the species.